Environmental Pressure from Pig Farming to Surface Water Quality Management in Yen Dung District Bac Giang Province - An, Ngo The; Lan, Ngo Phuong; Cong, Vo Huu; Duong, Nong Huu; Huong Giang, Nguyen Thi (VNU Journal of Science: Earth and Environmental Sciences, 2020)
This study focuses on the environmental pressure of waste generated from pig farming in Yen Dung district. Terrain analysis of the digital elevation model (DEM) was used to delineate the sub-basin map where pollutants accumulated. Then we combined this map with land use map and statistical data for determining the distribution of pollutant discharged sources. Based on the pollution load coefficient prescribed by the Vietnam Environment Administration, the loads from all sources, including pig farming, were estimated for entire sub-basins within the district. The results show that the pollutant load from pig farming accounts for a large proportion and creates a major pressure on the local environment. The pollutant from pig farming greatly influences the spatial distribution of pollutant loads across sub-basins. Therefore, special attention should be paid to the waste management at pig farms (households and farm) to ensure the effectiveness of the environmental protection for the communities. Keywords: livestock waste, pollutant load mapping, pig farming.